Financial Performance Analysis of Savings and Loan Cooperatives (KSP) Swasti Sari Malaka Branch - Pangastuti, Margareta Diana; Nalle, Frederic Winston (PT Inovasi Pratama Internasional, 2024)
This study aims to analyze the financial performance of Koperasi Swasti Sari Branch Malaka using financial ratios—liquidity, solvency, profitability, and activity ratios—from 2020 to 2023. The significance of this research lies in its contribution to understanding the financial resilience of cooperatives in Indonesia, particularly in rural and border areas. Using a descriptive quantitative approach, the analysis is based on secondary data obtained from financial reports, processed using Microsoft Excel tools. he results show that the average liquidity ratios indicate good short-term financial stability, with a Current Ratio of 151.68% and a Quick Ratio of 151.64%. The solvency ratio, Debt to Asset Ratio (DAR), averages 67.80%, reflecting controlled reliance on debt, though caution is advised for future financing. The profitability performance is excellent, as evidenced by the Net Profit Margin (NPM) of 67.94% and the Return on Assets (ROA) of 15.84%, indicating strong profitability management. However, the activity ratios highlight inefficiencies, with Cash Turnover averaging 2.13 times and Receivables Turnover at 0.09 times, underscoring the need for improved cash and receivable management. It is recommended that Koperasi Swasti Sari improve its cash and receivables management strategies to enhance operational efficiency, optimize liquidity, and maintain financial sustainability while prudently managing debt to ensure long-term growth.